Corruption and Social Structure: Theory, and Evidence from India - Christopher Kingston (BREAD Working Paper No. 075, 2004)
Corruption often poses a collective action problem: citizens or firms may each pay bribes in an effort to obtain preferential treatment, but would all benefit from a mutual commitment not to bribe. If they can sanction each other in other games, then by "linking" the games they may be able to overcome this "briber'sdilemma". Corruption will be less common in societies with an "integrated" social structure, in which individuals interact with different people for different purposes, than in a "collectivist" society in which people interact mainly within close-knit groups. We provide several examples and carry out an empirical test using Indian data to support the model.